2017
DOI: 10.1039/c7cs00324b
|View full text |Cite
|
Sign up to set email alerts
|

Cycloaddition reactions of enoldiazo compounds

Abstract: Enoldiazo esters and amides have proven to be versatile reagents for cycloaddition reactions that allow highly efficient construction of various carbocycles and heterocycles. Their versatility is exemplified by (1) [2+n]-cycloadditions (n = 3, 4) by the enol silyl ether units of enoldiazo compounds with retention of the diazo functionality to furnish α-cyclic-α-diazo compounds that are themselves subject to further transformations of the diazo functional group; (2) [3+n]-cycloadditions (n = 1–5) by metallo-eno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(66 citation statements)
references
References 183 publications
0
66
0
Order By: Relevance
“…Another example of the versatility of enol diazoacetates can also be seen in cycloaddition reactions (Cheng et al 2017). These compounds can react in different cycloaddition pathways to construct several carbocycles and heterocycles (Jadhav et al 2012, Xu et al 2013, Cheng et al 2015, Deng et al 2016.…”
Section: Substituent Modification In Diazocarbonyl Compoundsmentioning
confidence: 99%
“…Another example of the versatility of enol diazoacetates can also be seen in cycloaddition reactions (Cheng et al 2017). These compounds can react in different cycloaddition pathways to construct several carbocycles and heterocycles (Jadhav et al 2012, Xu et al 2013, Cheng et al 2015, Deng et al 2016.…”
Section: Substituent Modification In Diazocarbonyl Compoundsmentioning
confidence: 99%
“…Recently the transition metal catalyzed vinylcarbene approach to cycloaddition has shown considerable promise for highly chemo-, regio-, and enantio-selective cycloaddition reactions. Examples of [3+4]-, 9 [3+3]-, [10][11][12][13][14] [3+2]-, [14][15][16][17][18][19][20] and even a [3+1]- 21 and [3+5]- 22 cycloaddition reactions have been reported using dipolar metallo-vinylcarbenes, generally in high yields with low catalyst loadings. The transformations of silyl-protected enoldiazo compounds (Scheme 2) involve initial nucleophilic attachment to the electrophilic vinylogous position of the metallo-vinylcarbene followed by electrophilic addition to the original carbenic center with displacement of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…High stereocontrol has been achieved with silyl-protected enoldiazo-acetates, -acetamides, -ketones, and -sulfones in most of these cycloaddition reactions, and also with styryldiazoacetates in [3+2]cycloaddition reactions. Our earlier review of cycloaddition reactions involving silylprotected enoldiazo compounds 12 reported the breadth of these transformations mainly with diazoacetates and with dirhodium catalysts. This report documents the extensive growth in these reactions since 2016, their mechanistic implications for future expansion, and the applicability of chiral copper catalysts to compliment and improve previously documented performance with chiral dirhodium catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Diazo compounds have found a multitude of applications in synthetic chemistry and are versatile intermediates that can rapidly functionalize organic compounds in a single step. [1,2] In particular, diazo compounds and N-tosylhydrazones (diazo precursors) have attracted much attention as carbonyl equivalents in the construction of carbon-carbon double bonds. [3] Transition metal catalysts, such as palladium, are typically used in reactions with diazo compounds to synthesize C = C bonds.…”
mentioning
confidence: 99%